Desenvolvimento de função desejabilidade para redução de incidência de filés desagregados na industria de abate de pescados - Almeida, Thaise Pascoato de Oliveira (2020)
Fish is a food of high nutritional value and has been gaining market share in recent years, with tilapia being the most cultivated fish in Brazil, responsible for 57% of national fish production. Freshness and firmness are the main characteristics evaluated at the time of consumption and commercialization in fish. The change in the texture of the fish meat characterized as “soft and disaggregated filet” has characteristics similar to a PSE meat (Pale, Soft and Exudative), an anomaly affected in pigs and poultry, but little studied in fish. Thus, the present study aimed to characterize the disintegrated fillets for further development of a mathematical modulation that makes it possible to determine the incidence of PSE meat in Nile tilapia in the processing industries from the quality parameters used in the pre-slaughter management. For the development of the present work, Nile tilapia from a fish slaughterhouse located in Paraná western were used. The study was carried out in three stages, where the first aimed to characterize the disaggregated fillet, the second to determine the influence of the season on the incidence of the year and the third to develop a desirability function to reduce the incidence of disaggregated fillets in the fish slaughter industry. From the data obtained, it is believed that the disaggregated fillets are similar to the PSE meats, since in the characterization of the fillets the average pH value and L*(luminosity) value for normal fillets were 6.07 and 52.20 and for the disaggregated fillets were 5.94 and 55.40, however the influence of the season on their incidence was not found in this study, but it is believed that these are associated with the stress suffered in the ante-mortem. Believing that the incidence of disintegrated fillets is closely related to the management that precedes slaughter, a desirability function was developed that could determine optimal values for the quality standards of operations immediately before the slaughter of the animal. The function resulted in an overall desirability of an incidence of 0.63% of disintegrated fillets during production.